Fighting Forces of World War II at Sea - Miles, John C. (John Christian), 1960- (North Mankato, Minnesota : Capstone Press, a Capstone Imprint, 2020)
How did the forces that fought at sea affect the outcome of World War II? This book explores the ships and submarines that slugged it out to rule the seas during World War II, from stealthy U-boats to mighty battleships. Along the way, readers will discover the key battles, tactics, and weapons that helped propel the Allies to victory. Provides perspectives from both sides of the war; Appealing to readers who enjoy history and military topics; Provides a global approach to and perspective on World War II; Features not only the men, but also the brave women who fought and supported their countries during the war; Stunning historical photographs and fascinating war statistics bring the topics to life.
Keywords: World War, 1939-1945 -- Naval operations; Juvenile literature; Warships -- History -- 20th century; Juvenile literature; Submarines (Ships) -- History; 20th century; Juvenile literature; Navies; History -- 20th century; Juvenile literature; History; Juvenile works